2020
DOI: 10.1021/acs.analchem.9b05449
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection of miR-122 in Hepatotoxicity Using Dynamic Chemical Labeling Overcomes Stability and isomiR Challenges

Abstract: Circulating microRNAs are biomarkers reported to be stable and translational across species. MicroRNA-122 (miR-122) is a hepatocyte-specific microRNA biomarker for drug-induced liver injury (DILI). We developed a single molecule, dynamic chemical labeling (DCL) assay to directly detect miR-122 in blood. The DCL assay specifically measured miR-122 directly from 10 μL of serum or plasma without any extraction steps, with a limit of detection of 1.32 pM that enabled the identification of DILI. Testing of 192 huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…In the current study, we have demonstrated that for miR-126 this is not the case: significant degradation occurred if the sample was left unprocessed for 24hr. We have reported similar instability for miR-122 (Lopez-Longarela et al, 2020). We also demonstrated that hemolysis may increase the concentration of miR-126 present in the sample.…”
Section: Ll Open Accesssupporting
confidence: 74%
“…In the current study, we have demonstrated that for miR-126 this is not the case: significant degradation occurred if the sample was left unprocessed for 24hr. We have reported similar instability for miR-122 (Lopez-Longarela et al, 2020). We also demonstrated that hemolysis may increase the concentration of miR-126 present in the sample.…”
Section: Ll Open Accesssupporting
confidence: 74%
“…We have reported similar instability for miR-122. 41 We also demonstrated that hemolysis may increase the concentration of miR-126 present in the sample. Furthermore, despite reports that miRs are detected at similar concentrations in plasma and serum, plasma miR-126 was substantially higher than serum.…”
Section: Discussionmentioning
confidence: 59%
“…The detection may be done with any methodology (chemiluminescent, fluorescent, or colorimetric), depending on the type of modification the SMART-NB carries. The technology may be used for direct detection from several sources, including biofluids, avoiding RNA extraction, RT and/or PCR amplification and it has been validated in several contexts for miRNAs analysis [155][156][157][158][159].…”
Section: Chem-natmentioning
confidence: 99%